2019
DOI: 10.1088/1475-7516/2019/07/024
|View full text |Cite
|
Sign up to set email alerts
|

Testing modified gravity at cosmological distances with LISA standard sirens

Abstract: Modifications of General Relativity leave their imprint both on the cosmic ex-Contents A GW luminosity distance and the flux-luminosity relation 53 B Technical details on bigravity 55 B.1 Hassan-Rosen theory of bigravity 55 B.2 Details on the WKB approximation for bigravity 56References 58 5. In the presence of anisotropic stress, or in theories where tensors couple with additional fields already at linearised level (as in theories breaking spatial diffeomorphisms), the tensor evolution equation contains a "so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
391
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 247 publications
(410 citation statements)
references
References 238 publications
(467 reference statements)
17
391
0
2
Order By: Relevance
“…This behavior turns out to be completely generic to modified gravity models (scalar-tensor theories, nonlocal modifications of gravity, bigravity, etc.) [203]. For most models, the deviations from GR can be parametrized in terms of two parameters (Ξ 0 , n) as [195] d gw…”
Section: The Nature Of Dark Energymentioning
confidence: 99%
“…This behavior turns out to be completely generic to modified gravity models (scalar-tensor theories, nonlocal modifications of gravity, bigravity, etc.) [203]. For most models, the deviations from GR can be parametrized in terms of two parameters (Ξ 0 , n) as [195] d gw…”
Section: The Nature Of Dark Energymentioning
confidence: 99%
“…This behavior has been first found explicitly in scalar-tensor theories of the Horndeski class [31,33,[35][36][37] and in nonlocal infrared modifications of gravity [19,20]. The analysis in [41] showed that also scalar-tensor theories of the DHOST type, as well as bigravity, display this phenomenon, so an equation of propagation of the form (5) is completely generic and appears in all the best studied models of modified gravity. In some instances the effect is related to the time variation of the Newton constant (or, equivalently, of the Planck mass) that takes place in these models.…”
Section: Introductionmentioning
confidence: 80%
“…Similar issues concerning LISA and TianQin [39][40][41][42][43][44] have been investigated in Ref. [31,45,46]. Therefore, in this paper, we make a forecast for the prospect of Taiji in cosmological parameter estimation by using the simulated standard siren data.…”
Section: Introductionmentioning
confidence: 83%